MicroRNA: Function, Detection, and Bioanalysis - Dong, Haifeng; Lei, Jianping; Ding, Lin; Wen, Yongqiang; Ju, Huangxian; Zhang, Xueji (Chemical reviews, 2013)
The use of microRNA if the field of pharmaceutical sciences is discussed. In addition, several techniques for detecting miRNA are examined.